Encyclopedia of canonical ḥadīth - Juynboll, G. H. A. (Middle East and Islamic Studies E-Books Online, Collection 2007, ISBN: 9789004223028., 2007)
This encyclopedic work on Islam comprises English translations of all canonical ḥadīths, complete with their respective chains of transmission (isnāds). By conflating the variant versions of the same ḥadīth, the repetitiveness of its literature has been kept wherever possible to a minimum. The latest methods of isnād analysis, described in the general introduction, have been employed in an attempt to identify the person(s) responsible for each ḥadīth. The book is organized in the alphabetical order of those persons. These are the so-called 'common links'. Each of them is listed with the tradition(s) for the wording of which he can be held accountable, or with which he can at least be associated. Within each article, the traditions are referred to in bold figures in the numerical order as they were distilled from the more than 19,000 isnāds listed in Tuḥfat al-ashrāf bi ma'rifat al-aṭrāf by the Syrian ḥadīth scholar Yusuf born 'Abd ar-Raḥmān al-Mizzī (d. 742/1341). Medieval commentaries as well as assorted biographical lexicons were drawn upon to illustrate the text of each tradition in all theological, social, legal and other noteworthy aspects discernible in it. Thus no details of eschatology, superstitions, miraculous phenomena, Jahili practices et cetera were left without the clarifying comments of contemporary and later theologians, historians and ḥadīth experts culled from such works as the Fatḥ al-bārī, a major commentary of Bukhārī's Ṣaḥīḥ by Ibn Ḥajar al-'Asqalānī (d. 852/1448) or the commentary by Yaḥya born Sharaf an-Nawawī (d. 676/1277) of the Ṣaḥīḥ of Muslim born al-Ḥajjāj. The encyclopedia concludes with an exhaustive index and glossary of names and concepts, which functions at the same time as a concordance. In short, this work presents an indispensable sourcebook of the development of Islam in all its facets during the first three centuries since its foundation as reflected in canonical ḥadīth.